The Function of Stylistic Elements in Maintaining Literary Text Cohesion - Rahmatova Sitora Samadovna; Arustamyan Yana Yurievna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This thesis explores the role of stylistic elements in creating and sustaining cohesion within literary texts. Cohesion, defined as the grammatical and lexical linking that holds a text together, is fundamental to textual unity and reader comprehension. While linguistic theories emphasize devices such as reference, substitution, ellipsis, conjunction, and lexical cohesion (Halliday & Hasan, 1976), stylistic elements—including repetition, parallelism, metaphor, simile, alliteration, and syntactic patterning—extend these mechanisms by adding aesthetic, emotional, and thematic depth.